Imagined Engagements: Interpreting the Musical Relationship with the Canadian North - van den Scott, Jeffrey; van den Scott, Lisa-Jo K. (Qualitative Sociology Review, 2019)
In this article, we extend Benedict Anderson’s notion of imagined communities to examine the idea of an “imagined engagement” between or among people and groups that have not met. These imagined engagements include a blurring of temporal lines, as one group “interacts” with another’s past, present, or future. Imagined engagements are a form of failed interaction, and, as such, have their place in Goffman’s interaction order. We argue that musical language can comprise a meeting point of these engagements. We then demonstrate how two composers—one historic and one contemporary—have used the musical cultures of an Othered people, with a focus on Indigenous America, in an attempt to create a sense of community and common ties between the West and these Others—a sense of community in which the Othered have no part.